Preparation method of high-hardness wear-resistant coating coated with MS resin
A metal ion-catalyzed organic siloxane coating for MS resin addresses adhesion and wear resistance issues by forming a cross-linked network structure, enhancing scratch resistance and hardness through dual bonding.
Patent Information
- Application Number
- CN202411233587.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional silicone coatings struggle to adhere effectively to the surface of MS resin, leading to poor adhesion, hardness, and wear resistance, which is critical for applications in optical lenses and transparent windows.
A high-hardness wear-resistant coating is prepared using metal ion-catalyzed pre-hydrolysis condensation and coordination cross-linking of organic siloxane monomers, involving a specific formulation and thermal curing process to enhance adhesion and hardness on MS resin surfaces.
The coating achieves improved adhesion and wear resistance on MS resin surfaces through a dual bonding mechanism of hydrogen bonding and metal coordination chelation, resulting in enhanced scratch resistance and hardness.
Smart Images

Figure BDA0005027044910000121 
Figure BDA0005027044910000131 
Figure BDA0005027044910000132
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing MS resin protective coatings, and in particular relates to a method for preparing a high-hardness wear-resistant coating coated with MS resin. Background Art
[0002] MS resin, also known as methyl methacrylate-styrene copolymer (Methyl Methacrylate-Styrene Copolymer), is a synthetic polymer material. MS resin is copolymerized by methyl methacrylate (MMA) and styrene (ST). MS resin was developed in the early 20th century and gradually developed into an important engineering plastic in the following decades. It is mainly prepared by free radical polymerization, which involves copolymerizing MMA and ST under the action of an initiator to produce a resin material with excellent properties. MMA provides high transparency, good weather resistance and excellent optical properties; ST enhances the rigidity and mechanical strength of the material while reducing production costs. By adjusting the ratio of MMA and ST, the performance of MS resin can be regulated to achieve a balance between transparency, mechanical strength and processing performance. Based on the excellent performance of MS resin, it has a wide range of applications in optical fields such as optical lenses and optical instruments, building materials such as transparent windows and sound insulation boards, automotive industry such as car lampshades, and transparent protective screens for mobile phones and tablets.
[0003] Although MS resin has many excellent properties, its surface also inevitably has some technical problems. For example, the surface of MS resin is soft and easy to be scratched, which affects the appearance and transparency. Therefore, the surface protection of MS resin is particularly important.
[0004] Patent CN109651941A discloses a silicone-modified wear-resistant amphiphobic coating and a preparation method thereof. The amphiphobic coating of the invention is composed of perfluoropolyether trimethoxysilane with a molecular weight of 3000-5000, perfluoropolyether methyldimethoxysilane with a molecular weight of 3000-5000 and perfluoroalkyltrimethoxysilane with an alkyl group of heptyl, octyl, nonyl or decyl. A composite mixture of fluorinated polyether alkoxysilane and perfluoroalkyl siloxane of different structures is used to form an amphiphobic coating with a special three-dimensional structure on the surface of the substrate through spraying or evaporation. This special structure gives the coating excellent wear resistance and anti-fouling properties, and is used for glass and ceramic surfaces.
[0005] Patent CN114350262A discloses a bactericidal and antiviral ultra-wear-resistant organosilicon coating liquid and its preparation method, organosilicon coating and its preparation method, the invention is cured into a film with three components of epoxysilane, aminosilane and urea-based silane, these silanes are hydrolyzed to form a silanol structure, wherein aminosilane is a general-purpose aminosilane coupling agent, which can react with hydroxyl groups in inorganic substances, and can react with epoxysilane to form a long molecular chain polymer, thereby coupling two materials of different properties. However, these free amino groups have high alkalinity and high reactivity, and are prone to premature reactions during use and fail to achieve the expected results. The introduction of urea-based silane (-Si-CCC-NH-CO-NH2) can reduce the reactivity with epoxy groups, thereby maintaining a certain limit of working performance, so that the organosilicon coating liquid obtained by the invention is applied to glass, ceramics, marble, stainless steel, wood, PET, PC and PMMA surfaces.
[0006] Patent CN114672059A discloses a method for integrated wear-resistant and flame-retardant modification of the surface of polycarbonate (PC). The invention uses the method of surface infiltration of inorganic nanoparticles to modify polycarbonate. Through the action of a penetration-assisting solution and utilizing the characteristics of the destruction and reconstruction of the polycarbonate surface, inorganic nanoparticles with wear-resistant and flame-retardant effects are infiltrated into the surface, thereby achieving integrated wear-resistant and flame-retardant modification of polycarbonate.
[0007] Patent CN104927589A discloses an organic silicon wear-resistant hard coating and a preparation method thereof. The coating is composed of an epoxy resin, a silane coupling agent and an initiator. The initiator catalyzes the ring opening of the epoxy resin and cross-links with the silane coupling agent, thereby improving the bonding strength between the prepared coating liquid and the PMMA substrate.
[0008] Patent CN110903743A discloses a photocurable coating for a surface coating of a polyamide substrate. The invention improves the adhesion between the polyamide material (PA) and the coating by adding a low molecular weight acidic functional monomer to participate in the photocuring reaction.
[0009] Patent CN103172826A discloses an optical resin monomer with high scratch resistance and a preparation method thereof. The invention mixes raw materials such as CR-39, dimethyl terephthalate, propylene glycol, allyl alcohol and a polymer to obtain an optical resin monomer with high scratch resistance.
[0010] Patent CN11295602A discloses a method for manufacturing a light absorber, which irradiates a resin substrate CR-39 with an ion beam, then etches the irradiated resin substrate CR-39 with an alkaline solution to form a concave-convex surface on its surface, then covers the concave-convex surface to form a transfer body, and finally peels off the transfer body to obtain a light absorber with low reflectivity.
[0011] The above coating liquid is mainly for the surface of PC, PA, CR-39 and PMMA materials. For MS resin, due to the different composition structure, conventional silicone coating liquid is difficult to adhere to the surface of MS resin.
[0012] Therefore, a coating is designed to improve the adhesion between the coating liquid and the MS resin, thereby achieving hardness and wear-resistant protection for the MS resin, which has practical application value in the fields of optical lenses, transparent lampshade shells and transparent windows. Summary of the invention
[0013] In view of the deficiencies of the prior art, the present invention prepares a high-hardness wear-resistant coating with good adhesion, hardness and wear resistance to MS resin by metal ion-catalyzed pre-hydrolysis condensation and coordination cross-linking of organic siloxane monomers, so as to solve the problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents:
[0014] A method for preparing a high-hardness wear-resistant coating coated with MS resin, the preparation method comprising the following steps:
[0015] The organic silicon prepolymer, the mixed solvent, the leveling agent and the curing agent are mixed and stirred in a weight ratio of 40:20-60:1-3:1-3 to form a coating liquid;
[0016] The MS resin is completely immersed in the coating liquid, and then subjected to a thermal curing process at a pulling rate of 10 cm / min to 25 cm / min and 80° C. to 85° C. for 2 h to 3 h to obtain the high-hardness wear-resistant coating coated with the MS resin.
[0017] Furthermore, the preparation method of the organosilicon prepolymer comprises the following steps:
[0018] The organosiloxane monomer, organic solvent, metal ion catalyst and water are mixed and stirred in a mass ratio of 100:30-40:0.5-2:50-100 to be uniformly dispersed, and then ultrasonically treated at a power of 300W-400W for 5min-10min to obtain the organosilicon prepolymer.
[0019] Furthermore, the organosiloxane monomers include methyl orthosilicate, ethyl orthosilicate, methylpropyl dimethoxysilane, methylpropyl diethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, propyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, hexamethylcyclotrisiloxane, β-(3,4-epoxy The invention can be a combination of any one or more of trimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, vinyltriacetoxysilane, vinyltriacetoxysilane, methylphenyldimethoxysilane and phenylmethyldiethoxysilane.
[0020] Furthermore, the organic solvent includes any one or more of methanol, ethanol, isopropanol, butanol, methyl ethyl ketone, acetone, ETB, PM, propylene glycol methyl ether acetate and BCS.
[0021] Furthermore, the metal ion catalyst includes aluminum chloride, ferric chloride or zinc chloride.
[0022] Furthermore, the leveling agent includes dimethyl silicone oil, BYK333, DC57 or MONENG-S1154, and may also be other commercial silicone leveling agents, acrylic leveling agents or fluorocarbon leveling agents.
[0023] Further, the curing agent includes any one or more of dibutyltin dilaurate, dibutyltin diacetate, benzyldimethylamine, N,N-dimethylcyclohexylamine, benzyltriethylammonium chloride, dodecyltrimethylammonium chloride, tetrabutylammonium chloride, ammonium hydroxide, diethylenetriamine and N-aminoethylpiperazine.
[0024] A high-hardness wear-resistant coating coated with MS resin prepared by the preparation method.
[0025] An application of the high-hardness wear-resistant coating coated with MS resin prepared by the preparation method on the surface of MS resin.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention creatively designs a high-hardness wear-resistant coating for MS resin. Under the action of metal ion catalyst, the organosiloxane monomer containing a silicon-oxygen skeleton is subjected to the action of metal ion catalyst. On the one hand, the metal ion catalyst exerts the catalytic hydrolysis effect of Lewis acid to hydrolyze the silicon-oxygen bonds in the organosiloxane monomer to form silicon hydroxyl groups, and then forms an organosilicon prepolymer with a cross-linked network structure through ultrasonic prepolymerization. On the other hand, due to the metal coordination chelation effect of metal ions, it can form a coordination bond with the organosilicon prepolymer. When the MS resin is immersed in a coating liquid composed of an organosilicon prepolymer, a mixed solvent, a leveling agent and a curing agent, in an appropriate temperature environment, the coating liquid forms a dual surface synergistic bonding effect of physical adsorption of hydrogen bonding and chemical cross-linking including metal coordination with the surface of the MS resin, thereby firmly fixing the coating liquid on the surface of the MS resin, improving the adhesion of the coating liquid on the surface of the MS resin, and further achieving wear protection and hardness protection for the MS resin.
[0028] (2) It can be seen from Example 6 and Comparative Examples 1 to 3 that although hydrochloric acid, sulfuric acid and p-toluenesulfonic acid have acid-catalyzed hydrolysis and condensation functions, since they do not contain metal ions, when the coating liquid is solidified on the surface of the MS resin, there is only a physical effect of hydrogen bonding, and there is a lack of adsorption effect of chemical cross-linking of metal coordination chelation. Therefore, the coating liquid obtained in Comparative Examples 1 to 3 has poor performance in hardness, adhesion and scratch resistance. Therefore, the catalyst used in the preparation of the silicone prepolymer of the present invention has specific requirements.
[0029] (3) It can be seen from Example 6 and Comparative Examples 4 to 5 that the coating liquid of the present invention has a poor bonding effect on the coating of resin materials such as PA and PMMA, resulting in poor hardness, adhesion and scratch and wear resistance. Therefore, the use of the coating liquid of the present invention has certain specific requirements on the substrate. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0032] Preparation Example 1:
[0033] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0034] 100 g of methyl orthosilicate, 30 g of methanol, 0.5 g of aluminum chloride and 50 g of deionized water were mixed and added to a flask. The mixture was first stirred at 200 r / min with a magnetic stirrer until uniformly dispersed. The flask was then placed in an ultrasonic cleaner, the ultrasonic power was set to 300 W, and ultrasonic treatment was started for 5 minutes to obtain a silicone prepolymer.
[0035] Preparation Example 2:
[0036] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0037] 20 g of methyl orthosilicate, 20 g of ethyl orthosilicate, 20 g of methylpropyldimethoxysilane, 20 g of methylpropyldiethoxysilane, 20 g of methyltrimethoxysilane, 10 g of ethanol, 10 g of isopropanol, 10 g of butanol, 0.5 g of aluminum chloride and 60 g of deionized water were mixed and added to a flask, first stirred with a magnetic stirrer at a speed of 200 r / min until uniformly dispersed, and then the flask was placed in an ultrasonic cleaning machine, the ultrasonic power was set to 320 W, and then ultrasonic treatment was started for 6 minutes to obtain a silicone prepolymer.
[0038] Preparation Example 3:
[0039] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0040] 20 g of methyltriethoxysilane, 20 g of propyltriethoxysilane, 20 g of 3-aminopropyltriethoxysilane, 20 g of 3-glycidyloxypropyltrimethoxysilane, 20 g of 3-glycidyloxypropyltriethoxysilane, 17 g of PM (propylene glycol monomethyl ether), 18 g of propylene glycol methyl ether acetate, 1 g of ferric chloride and 70 g of deionized water are mixed and added to a flask, first stirred with a magnetic stirrer at a speed of 250 r / min until uniformly dispersed, then placed the flask in an ultrasonic cleaning machine, set the ultrasonic power to 340 W, and then start ultrasonic treatment for 7 minutes to obtain a silicone prepolymer.
[0041] Preparation Example 4:
[0042] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0043] 20 g of 3-glycidyloxypropylmethyldimethoxysilane, 20 g of hexamethylcyclotrisiloxane, 20 g of β-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 20 g of 3-methacryloxypropyltrimethoxysilane, 20 g of vinyltrimethoxysilane, 18 g of methyl ethyl ketone, 17 g of acetone, 1.5 g of ferric chloride and 80 g of deionized water were mixed and added to a flask, first stirred with a magnetic stirrer at a speed of 250 r / min until uniformly dispersed, and then the flask was placed in an ultrasonic cleaning machine, the ultrasonic power was set to 360 W, and then ultrasonic treatment was started for 8 minutes to obtain a silicone prepolymer.
[0044] Preparation Example 5:
[0045] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0046] 20 g of vinyltriethoxysilane, 20 g of 1,2-bis(triethoxysilyl)ethane, 20 g of phenyltrimethoxysilane, 20 g of phenyltriethoxysilane, 20 g of diphenyldimethoxysilane, 40 g of ETB (ethylene glycol tert-butyl ether), 2 g of zinc chloride and 90 g of deionized water were mixed and added to a flask, first stirred with a magnetic stirrer at a speed of 300 r / min until uniformly dispersed, and then the flask was placed in an ultrasonic cleaning machine, the ultrasonic power was set to 380 W, and then ultrasonic treatment was started for 9 minutes to obtain a silicone prepolymer.
[0047] Preparation Example 6:
[0048] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0049] 20 g of diphenyldiethoxysilane, 20 g of vinyltriacetoxysilane, 20 g of vinyltriacetoxysilane, 20 g of methylphenyldimethoxysilane, 20 g of phenylmethyldiethoxysilane, 40 g of BCS (ethylene glycol butyl ether), 2 g of zinc chloride and 100 g of deionized water are mixed and added to a flask, first stirred with a magnetic stirrer at a speed of 300 r / min until uniformly dispersed, then the flask is placed in an ultrasonic cleaning machine, the ultrasonic power is set to 400 W, and then ultrasonic treatment is started for 10 minutes to obtain a silicone prepolymer.
[0050] Preparation Example 7:
[0051] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0052] The zinc chloride in Preparation Example 6 was replaced by hydrochloric acid, and the other conditions remained the same as in Preparation Example 6.
[0053] Preparation Example 8:
[0054] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0055] The zinc chloride in Preparation Example 6 was replaced by sulfuric acid, and the other conditions remained the same as in Preparation Example 6.
[0056] Preparation Example 9:
[0057] The preparation method of the organosilicon prepolymer specifically includes the following steps:
[0058] The zinc chloride in Preparation Example 6 was replaced by p-toluenesulfonic acid, and the other conditions were the same as those in Preparation Example 6.
[0059] Embodiment 1:
[0060] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0061] 40 parts by weight of the silicone prepolymer of Preparation Example 1, 20 parts by weight of a mixed solvent (methanol and ethanol mixed in equal amounts), 1 part by weight of a leveling agent dimethyl silicone oil, and 1 part by weight of a curing agent dibutyltin dilaurate were mixed and stirred at a speed of 100 r / min for 30 minutes to form a coating liquid. The MS resin was placed in an ultrasonic cleaning machine, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 10 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 80°C for 2 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0062] Embodiment 2:
[0063] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0064] 40 parts by weight of the silicone prepolymer of Preparation Example 2, 30 parts by weight of a mixed solvent (mixed by isopropanol and ethanol in equal amounts), 1 part by weight of a leveling agent dimethyl silicone oil, and 1.5 parts by weight of a curing agent (mixed by dibutyltin diacetate and benzyldimethylamine in equal amounts) were mixed and stirred at a speed of 100 r / min for 30 minutes to form a coating liquid. The MS resin was placed in an ultrasonic cleaning machine, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 15 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 80°C for 2 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0065] Embodiment 3:
[0066] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0067] 40 parts by weight of the silicone prepolymer of Preparation Example 3, 40 parts by weight of a mixed solvent (acetone and PM mixed in equal amounts), 1.5 parts by weight of a leveling agent BYK333 and 1.5 parts by weight of a curing agent (N,N-dimethylcyclohexylamine, benzyltriethylammonium chloride and dodecyltrimethylammonium chloride mixed in equal amounts) were mixed and stirred at a speed of 200 r / min for 20 minutes to form a coating liquid. The MS resin was placed in an ultrasonic cleaning machine, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 15 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 85°C for 2 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0068] Embodiment 4:
[0069] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0070] 40 parts by weight of the organosilicon prepolymer of Preparation Example 4, 50 parts by weight of a mixed solvent (a mixture of acetone and PM in equal amounts), 2 parts by weight of a leveling agent DC57 and 2 parts by weight of tetrabutylammonium chloride were mixed and stirred at a speed of 200 r / min for 20 minutes to form a coating liquid. The MS resin was placed in an ultrasonic cleaning machine, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 20 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 85°C for 3 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0071] Embodiment 5:
[0072] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0073] 40 parts by weight of the organosilicon prepolymer of Preparation Example 5, 60 parts by weight of a mixed solvent (equal amounts of ethanol and acetone), 2.5 parts by weight of a leveling agent DC57 and 2.5 parts by weight of a curing agent (equal amounts of ammonium hydroxide and diethylenetriamine) were mixed and stirred at a speed of 300 r / min for 10 minutes to form a coating liquid. The MS resin was placed in an ultrasonic cleaning machine, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 20 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 80°C for 3 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0074] Embodiment 6:
[0075] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0076] 40 parts by weight of the organosilicon prepolymer of Preparation Example 6, 60 parts by weight of a mixed solvent (methanol and ethanol mixed in equal amounts), 3 parts by weight of a leveling agent MONENG-S1154 and 3 parts by weight of N-aminoethylpiperazine were mixed and stirred at a speed of 300 r / min for 10 min to form a coating liquid. The MS resin was placed in an ultrasonic cleaner, cleaned with deionized water and the surface moisture was dried, and then the dried MS resin was completely immersed in the coating liquid, and the MS resin was completely pulled upward out of the coating liquid at a pulling speed of 25 cm / min, and then the MS resin immersed in the coating liquid was placed in an environment of 85°C for 3 hours of thermal curing treatment, and naturally cooled to obtain a high-hardness wear-resistant coating coated with MS resin.
[0077] Comparative Example 1:
[0078] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0079] The organosilicon prepolymer in Example 6 was replaced by the organosilicon prepolymer of Preparation Example 7, and the other conditions remained the same as those in Example 6.
[0080] Comparative Example 2:
[0081] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0082] The organosilicon prepolymer in Example 6 was replaced by the organosilicon prepolymer of Preparation Example 8, and the other conditions remained the same as in Example 6.
[0083] Comparative Example 3:
[0084] A method for preparing a high-hardness wear-resistant coating coated with MS resin, specifically comprising the following steps:
[0085] The organosilicon prepolymer in Example 6 was replaced by the organosilicon prepolymer of Preparation Example 9, and the other conditions remained the same as in Example 6.
[0086] Comparative Example 4:
[0087] The MS resin in Example 6 was replaced by PMMA resin, and the other conditions remained the same as in Example 6.
[0088] Comparative Example 5:
[0089] The MS resin in Example 6 was replaced by PA resin, and the other conditions remained the same as in Example 6.
[0090] The hardness and adhesion of the high hardness wear-resistant coatings obtained by MS resin, Examples 1 to 6 and Comparative Examples 1 to 5 were measured according to "GB / T6739-2022 Paint and Varnish Pencil Method for Determination of Paint Film Hardness" and "GB / T9286-2021 Paint and Varnish Scratching Test". The results are as follows:
[0091]
[0092]
[0093] The MS resin, the high hardness wear-resistant coatings obtained in Examples 1 to 6 and Comparative Examples 1 to 5 were rubbed 20 times at the same speed with 0000# steel wool loaded with a 200g weight, and then the wear conditions of the surfaces were observed, which were divided into no scratches, basically no scratches, slight scratches, and severe scratches. The statistical results are shown in the following table:
[0094]
[0095]
[0096] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a high-hardness wear-resistant coating coated with MS resin, It is characterized in that The preparation method comprises the following steps: The organic silicon prepolymer, the mixed solvent, the leveling agent and the curing agent are mixed and stirred in a weight ratio of 40:20-60:1-3:1-3 to form a coating liquid; The MS resin is completely immersed in the coating liquid, and then subjected to a thermal curing process at a pulling rate of 10 cm / min to 25 cm / min and 80° C. to 85° C. for 2 h to 3 h to obtain the high-hardness wear-resistant coating coated with the MS resin.
2. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 1, It is characterized in that The preparation method of the organosilicon prepolymer comprises the following steps: The organosiloxane monomer, organic solvent, metal ion catalyst and water are mixed and stirred in a mass ratio of 100:30-40:0.5-2:50-100 to be uniformly dispersed, and then ultrasonically treated at a power of 300W-400W for 5min-10min to obtain the organosilicon prepolymer.
3. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 2, It is characterized in that The organosiloxane monomers include methyl orthosilicate, ethyl orthosilicate, methylpropyl dimethoxysilane, methylpropyl diethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, propyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, hexamethylcyclotrisiloxane, β-(3,4-epoxycyclohexane) The invention can be a combination of any one or more of trimethoxysilane, 1,2-bis(triethoxysilyl)ethane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, vinyltriacetoxysilane, vinyltriacetoxysilane, methylphenyldimethoxysilane and phenylmethyldiethoxysilane.
4. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 2, It is characterized in that The organic solvent includes any one or more of methanol, ethanol, isopropanol, butanol, methyl ethyl ketone, acetone, ETB, PM, propylene glycol methyl ether acetate and BCS.
5. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 2, It is characterized in that The metal ion catalyst includes aluminum chloride, ferric chloride or zinc chloride.
6. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 1, It is characterized in that The leveling agent includes dimethyl silicone oil, BYK333, DC57 or MONENG-S1154 。 7. A method for preparing a high-hardness wear-resistant coating coated with MS resin according to claim 1, It is characterized in that The curing agent includes any one or more of dibutyltin dilaurate, dibutyltin diacetate, benzyldimethylamine, N,N-dimethylcyclohexylamine, benzyltriethylammonium chloride, dodecyltrimethylammonium chloride, tetrabutylammonium chloride, ammonium hydroxide, diethylenetriamine and N-aminoethylpiperazine.
8. A high hardness wear-resistant coating coated with MS resin obtained by the method for preparing a high hardness wear-resistant coating coated with MS resin as claimed in any one of claims 1 to 7.
9. Use of the high hardness wear-resistant coating coated with MS resin prepared by the method for preparing the high hardness wear-resistant coating coated with MS resin as claimed in any one of claims 1 to 7 or the high hardness wear-resistant coating coated with MS resin as claimed in claim 8 on the surface of MS resin.
Citation Information
Patent Citations
Catalyst-containing metal silicon oligomer, method for manufacturing same, and application for catalyst-containing metal silicon oligomer
CN106471001A
Organic silicon transparent flexible hard coating layer material and preparation method thereof
CN112876986A
Weather-resistant hard coat composition
JP2000281970A
Abrasion resistant coatings by siloxane oligomers
US20060235178A1
Method for Preparing Organopolysiloxane Resins
US20190153169A1
